Association of the expression levels in the longissimus muscle and a SNP in the CDC10 gene with marbling in Japanese Black beef cattle. (October 2015) - Tong, B.; Gao, G.Q.; Muramatsu, Y.; Ohta, T.; Kose, H.; Li, G.P.; Fatchiyah, F.; Yamada, T.
Abstract: The septin 7 ( CDC10 ) gene, involved in cellular proliferation, has been previously shown to be expressed at different levels in the longissimus muscle (LM) between low-marbled and high-marbled steer groups by differential-display PCR. It is located within the genomic region of a quantitative trait locus for marbling, and thus was considered as a positional functional candidate gene for marbling. In this study, we showed that the CDC10 expression levels in the LM were positively correlated with marbling in Japanese Black (JB) steers ( P < 0.0001). Further, an association analysis indicated that a SNP in the promoter region of the CDC10 gene was associated with marbling using 99 JB sires ( P = 0.03) and 542 JB paternal half-sib progeny steers from a sire homozygous for G allele at the SNP ( P < 0.0001). These findings suggest possible effects of the expression levels in the LM and the SNP of the CDC10 gene on marbling in JB cattle. Highlights: The CDC10 gene is related to cellular proliferation and located in a QTL region for marbling trait in Japanese Black cattle. The CDC10 expression level is positively correlated with marbling trait in Japanese Black cattle. The CDC10 expression level is higher in high-marbled Japanese Black steers than low-marbled Japanese Black steers. A SNP (NCBI_ss1388116468) in the promoter region of the CDC10 gene is associated with marbling trait. The CDC10 SNP may be useful for effective marker-assisted selection to increase the level of marbling.